Tax Avoidance. - Bond, S; Gammie, M; Whiting, J (Institute for Fiscal Studies, 2006)
Summary • The government’s efforts to tackle tax avoidance have become more high-profile in recent years. Measures to ‘protect revenues’ announced since the 2002 Budget alone are estimated to be raising about £4½ billion this year. • The traditional distinction between illegal tax evasion and legal tax avoidance (or planning) has been complicated by the efforts of the authorities to have some forms of avoidance seen as unacceptable even if they satisfy the letter of the law. In some areas, the government is now threatening to use retrospective legislation to ensure that taxpayers contribute what ministers regard as their ‘fair share’. • The Tax Avoidance Disclosure regime is the most important recent legislative development in tackling avoidance. It appears to have been successful from the government’s point of view, judging by the volume of disclosures made and the blocking measures deployed to halt arrangements it sees as unacceptable. • The authorities are also highlighting to senior executives the risk to their reputation of being found to engage in unacceptable tax avoidance, while leaving it unclear exactly what is unacceptable. This may help to raise revenue in the short run, but is also likely to make the UK a less attractive location for internationally mobile companies and individuals.